2021
DOI: 10.48550/arxiv.2111.00898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Availability Attacks Create Shortcuts

Da Yu,
Huishuai Zhang,
Wei Chen
et al.

Abstract: Indiscriminate data poisoning attacks, which add imperceptible perturbations to training data to maximize the test error of trained models, have become a trendy topic because they are thought to be capable of preventing unauthorized use of data. In this work, we investigate why these perturbations work in principle. We find that the perturbations of advanced poisoning attacks are almost linear separable when assigned with the target labels of the corresponding samples, which hence can work as shortcuts for the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Prior work has observed that the noise that poisons supervised learning tends to cluster according to the original class labels, and is linearly separable (Yu et al, 2021). We apply the same test on noise for attacking SimCLR and find the noise is not linearly separable.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior work has observed that the noise that poisons supervised learning tends to cluster according to the original class labels, and is linearly separable (Yu et al, 2021). We apply the same test on noise for attacking SimCLR and find the noise is not linearly separable.…”
Section: Discussionmentioning
confidence: 93%
“…We first show that indiscriminate poisoning attacks on supervised learning do not work well in the face of contrastive learning. Indiscriminate poisoning attacks against supervised learning tend to generate poisoning perturbations that are clustered according to the original class labels (Yu et al, 2021). Such a design is unlikely to be effective against contrastive learning since its representation learning does not involve any class labels.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [75] suggest explaining the success of availability attacks from the perspective of shortcuts. They further adopt pre-trained models to extract useful features for mitigating model reliance on the shortcuts.…”
Section: Supplementary Material: Can Adversarial Training Be Manipula...mentioning
confidence: 99%
“…Note that we consider the effectiveness of adding a small portion of poisoned data to D tr in this paper. While some other works (e.g., Huang et al (2021); Yu et al (2021); Fowl et al (2021)) consider a different problem: the attacker can directly modify up to the entire D tr . In practice, manipulating the existing D tr is not always feasible, while it is much easier for an attacker to add poisoned samples: for example, an attacker can actively manipulate datasets by sending corrupted samples directly to a dataset aggregator such as a chatbot, a spam filter, or user profile databases; the attacker can also passively manipulate datasets by placing poisoned data on the web and waiting for collection.…”
Section: Introductionmentioning
confidence: 99%